The Stagnation of Brazil's Exports: Reply - Leff, Nathaniel H. (Quarterly Journal of Economics, 1972)
Journal Article The Stagnation of Brazil's Exports: Reply Get access Nathaniel H. Leff Nathaniel H. Leff Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 3, August 1972, Pages 508–510, https://doi.org/10.2307/1880810 Published: 01 August 1972